LÂMPADA COMPACTA COM LEDS INTEGRANDO UM SISTEMA DE ILUMINAÇÃO DE EMERGÊNCIA - Fraytag, Jeferson; Pinto, Rafael A.; Cosetin, Marcelo R.; Cervi, Murilo; Campos, Alexandre; Prado, Ricardo N. D. (Salão do Conhecimento, 2013)
Resumo